Modeling the Interaction of Carbon Monoxide with Flexible Graphene: From Coupled Cluster Calculations to Molecular‐Dynamics Simulations. Issue 6 (13th February 2018) - Wilson, Jake; Faginas‐Lago, Noelia; Vekeman, Jelle; Cuesta, Inmaculada G.; Sánchez‐Marín, José; Sánchez de Merás, Alfredo
Abstract: The interaction of CO with graphene was studied at different theoretical levels. Quantum‐mechanical calculations on finite graphene models with the use of coronene for coupled cluster calculations and circumcoronene for B97D calculations showed that there was no preferential site for adsorption and that the most important factor was the orientation of CO relative to graphene. The parallel orientation was preferred, with binding energies around 9 kJ mol −1 at the CCSD(T) and B97D levels, which was in good agreement with experimental findings. From a large number of CO–circumcoronene and CO–CO interactions, computed at different distances and randomly generated orientations, parameters were fit to the improved Lennard–Jones potential. Such potentials, together with others describing the intramolecular dynamics of graphene, were subsequently employed in classical molecular‐dynamics simulations of the adsorption of CO on graphene by using the canonical ensemble. The obtained results showed that the introduction of flexibility in graphene, which simulated the effects associated to curvature of the surface, diminished the adsorption level and that, as expected, adsorption also diminished with temperature. Abstract : Stuck on graphene : The adsorption of carbon monoxide on graphene is modeled at several levels of theory running from CCSD(T) calculations to molecular‐dynamics (MD) simulations. The results show that the introduction of flexibility in graphene, which simulates the effects associated to curvature of the surface, diminish the adsorption level and that, as expected, adsorption also diminishes with temperature.